THE INFLUENCE OF WORKLOAD ON EMPLOYEE PERFORMANCE AT CLASS IIA LUBUKLINGGAU PENITENTIARY - Febrioylas, Dito; Wibowo, Padmono (Universitas Nusa Cendana, 2025)
Performance is the result of carrying out the tasks assigned to officers as a form of responsibility to the organization. The performance of an officer is the main support in achieving organizational goals. There are many factors that can affect performance, one of which is workload. This study aims to determine the effect of workload on the performance of officers at Class IIA Lubuklinggau Correctional Facility. This study uses quantitative research methods using a causal design. The data is collected through filling out questionnaires given to research respondents, as well as several sources of books, journals, and articles that have the same topic as the research. The sampling technique used is probability sampling with random sampling type, and the calculation to determine the number of samples used the slovin formula so that the number of samples obtained is 69 people. The data from the questionnaire obtained was then analyzed by descriptive analysis test through simple linear regression analysis, determination test, and significance test using the IBM SPSS Statistics 25 application. The result of the analysis is that there is an influence of workload on performance with an influence value of 73.3%. The conclusion of this study is that there is a positive and significant influence between workload and employee performance at the Class IIA Correctional Institution Lubuklinggau. Keywords : Workload; Performance; Correctional